Effect of occlusal splint treatment on the temperature of different muscles in patients with TMD - Barão, Valentim Adelino Ricardo [UNESP]; Gallo, Ana Kelly Garcia [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Garcia, Alicio Rosalino [UNESP]; Assunção, Wirley Goncalves [UNESP] (Japan Prosthodontic Society, 2011)
Purpose: The aim of this study was to evaluate the effect of occlusal splint treatment on the temperature of masseter (inferior, intermediate and superior), anterior temporal, digastric and trapezius muscles in patients with temporomandibular disorder (TMD). Materials and methods: Thirty patients (6 male and 24 female) aged from 16 to 57 years (mean 37.8. ± 11.4 years) were selected. The patients were diagnosed with muscular TMD by clinical examination (application of Research Diagnostic Criteria questionnaire and physical examination). Occlusal splints in acrylic resin were inserted in all patients with a weekly follow-up. The superficial thermography (°C) on the both sides of the muscles was performed using a digital thermometer in a controlled temperature room. This procedure was performed before occlusal splint insertion (patient with pain) and after the completion of the treatment (patient without pain). The data were analyzed by 2-way repeated-measures ANOVA and means were compared by Tukey HSD test (P< .05). Results: After occlusal splint treatment a significant increase in temperature was observed in each muscle, both in the right and left sides. When the muscles were compared in the same period (before or after therapy) there was no significant difference among them. Conclusion: It can be concluded that the use of occlusal splint promoted a significant increase on the muscles temperature. There was symmetry in the temperature of muscles on the right and left sides both before and after the treatment. © 2010 Japan Prosthodontic Society.
Keywords: Muscle; Occlusal splint; Temporomandibular disorder; Thermography; adolescent; adult; body temperature; dental equipment; female; human; male; masseter muscle; middle aged; pathophysiology; physiology; temporomandibular joint disorder; Adolescent; Adult; Body Temperature; Female; Humans; Male; Masseter Muscle; Middle Aged; Occlusal Splints; Temporomandibular Joint Disorders; Young Adult